Macroeconomic Impact of Refugee Inflow on West African Countries - Nkwatoh, Louis Sevitenyi; Ibrahim, Kekere Sule (Yayasan Ahmar Cendekia Indonesia, 2021)
This study investigated the macroeconomic effect of refugee inflow on West African Countries using a panel vector autoregressive approach over the period 1992 to 2018. Our results provide evidence that a positive refugee shock induces a positive effect on GDP per capita, government consumption and labour force. On the other hand, the effect of a shock to refugee exerts a negative effect on the fiscal balance of host Countries. The overall result from the variance decomposition indicates that refugees prefer to migrate to Countries with better economic activities as reflected by the GDP per capita and labour supply, even though the magnitude of contribution of refugees to economic activities is small and significant only in the short run. Hence, refugees do not constitute an economic burden to West African States, but however induce a negative effect on their fiscal balance via extra budgetary expenditure. This calls for a global response to refugee crisis with respect to its fiscal implication on host Countries. This may go a long way in averting another circle of crisis because refugees often exacerbate the worsening economic and social problems of host Countries, leading to increase in government consumption.